Identification of factors associated with hand hygiene adherence as a support for creating curriculum for nurses training – a multivariate analysis - Garus-Pakowska, Anna (Journal of Medical Science, 2020)
Aim. Handwashing is the easiest way to prevent infection but is often neglected. The purpose of the study was to identify the barriers limiting the respect for hygiene procedures by nurses. Material and Methods. The study involved direct quasi-participant observation and a questionnaire of 11 nurses in six wards of three hospitals in Poland. Results. In total,1,195 observations were conducted in which 3,355 activities requiring hygiene procedures were observed over 8 months. The nurses’ knowledge of proper hand hygiene and infection prevention principles were unsatisfactory, with an average value of correct answers in the knowledge test of 8.7 (Max = 15). The univariate analysis indicated the following barriers in hand hygiene: emergencies, allergies, or too few dispensers. In multivariate analysis, the application of hygiene procedures depended on the level of education (higher education – worse compliance with the rules) and subjective conviction that handwashing/glove use was important. Conclusion. Educational programmes on hand hygiene should focus on the World Health Organisation indications that glove use is not a substitute for handwashing.